2022
DOI: 10.4103/ijnmr.ijnmr_279_20
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Developmentally Supportive Education Program on Nursing Knowledge of Retinopathy of Prematurity in Neonatal Intensive Care Unit

Abstract: Background: Retinopathy of Prematurity (ROP) is a preventable cause of childhood blindness. India accounts for nearly 10% of the worldwide estimate of blindness and visual impairment due to ROP. Nurses are pillars of neonatal intensive care units (NICUs) and play a critical role in the prevention and management of ROP. The primary aim of this study was to evaluate the effect of developmentally supportive education program on knowledge regarding prevention and management of ROP among nurses working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The results of the study showed that knowledge and attitude levels after the intervention were considerably greater than those before it. Thus, the researcher came to the conclusion that the most effective way to prevent cataracts and postpone their emergence in high-risk individuals is to educate the community about the self-instructional module [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study showed that knowledge and attitude levels after the intervention were considerably greater than those before it. Thus, the researcher came to the conclusion that the most effective way to prevent cataracts and postpone their emergence in high-risk individuals is to educate the community about the self-instructional module [ 28 ].…”
Section: Discussionmentioning
confidence: 99%